PENANGANAN KARGO UDARA PADA PT. ANGKASA PURA DI BANDARA SULTAN SYARIF KASIM II PEKANBARU - Damanik, Arnold; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Air cargo handling is a series of work processes for completing cargo when it is received until it is loaded onto an aircraft for transportation from one city to another at home and abroad. The aim of this research is to determine the implementation and obstacles that occur in handling goods delivery via air at Kargo PT. Angkasa Pura Sultan Syarif Kasim II Airport Pekanbaru. This research uses a qualitative method which aims to gain an in-depth understanding of the air cargo handling process at PT. Angkasa Pura at Sultan Syarif Kasim II Airport Pekanbaru. This research focuses on the factors that influence the handling of shipping goods, starting from reservations, goods entering the warehouse, checking goods, checking documents, to information on shipping goods, as well as improving services at the airport cargo. This research uses interviews, observation and documentation to detail the matters involved in air cargo handling, with the hope of making a new contribution to tourism development, especially in the delivery of goods. Keywords: Handling, Air Cargo, Reservations, Documents, Information